Perkembangan Pranata Sosial Berbasis Hukum Keluarga Islam di Indonesia - Abdul Hafiz (Jurnal Madania)
Islamic teaching preached by Muhammad saw contained verious norms- moral norm, legal norm, and social norm- have been institutionalized in the Islamic community as well as partly transformed into social institutions. The more revelations received by Muhammad the more norms conveyed to humans, and the more types of social institutions arise. When Muhammad was in Mecca while performing education institutions, he focused his attention on engrafting social norms. Dealing with marriage circumstances, a lot of changes of legal norms were regulated by the Marriage Code of Number 1 1974. The changes do not mean an old thing changes to new or a current thing differs from the past. The change often means to replace something to another one which has been exactly existed but not popular. Allowing woman becomes a judge, for instance, is one of the law changes that the former law did not allow her as a judge because of following certain sect. According to other sects, such allowing is not something new, but it has been existed since classical Islamic era. The change also means adopting certain concept and it is modified then. Adopted child is forbidden in Islam, but the Islamic Legal Compilation allowed it with modification.